ChemInform Abstract: Experimental Investigation of Phase Equilibria in the Co—Hf System. Issue 13 (March 2015) - Lu, Xingxu; Cheng, Kaiming; Liu, Shuhong; Li, Kai; Zheng, Feng; Du, Yong
Abstract Phase equilibria in the Co‐Hf binary system are investigated by XRD, TEM, SEM, electron probe microanalysis, and DSC on annealed and as‐cast alloys.